Monopoles, vortices and confinement in SU(3) gauge theory - Biagio Lucini (Physics Letters B, 2000)
We compute, in SU(3) pure gauge theory, the vacuum expectation value (vev) of the operator which creates a $Z_3$ vortex wrapping the lattice through periodic boundary conditions (dual Polyakov line). The technique used is the same already tested in the SU(2) case. The dual Polyakov line proves to be a good disorder parameter for confinement, and has a similar behaviour to the monopole condensate. The new features which characterise the construction of the disorder operator in SU(3) are emphasised.